Need analysis of development on career readiness module using Fuzzy Delphi Method (FDM) - Mahmud, Mohd Izwan; Mohd Noah, Sidek; Wan Jaafar, Wan Marzuki; Amat, Salleh; Abu Bakar, Abu Yazid (Sciendo, 2022)
Career development among university students is a transition between education and career readiness to determine graduate employability. This transition process demands students have education and career knowledge, high skills, problem-solving skills, and decision-making skills. This study aimed to identify the needs of career readiness module development that could be used for the students of public universities by using the Fuzzy Delphi Method (FDM). The descriptive research method was used to analyze the needs of career readiness module. The research samples were twelve counselling practitioners from different public universities. Data was collected using a set of a questionnaire consisting of five main themes with 15 items. The data were analyzed using the FDM method to obtain an expert consensus of module development needs. The research findings showed that the experts' consensus agrees for all five themes, with the level of agreement showing a value of more than 75% and a threshold value ≤ 0.2. The implications of this research can assist in the in-depth exploration of career module development that fulfills the issue of university students' career readiness. Apart from that, appropriate career theory can also be identified to serve as the basis of module development. Therefore, follow-up studies should focus on the development of career modules and conduct a study of the module effectiveness among the population of university students.